Multi-Dimensional Professional Communication Programme for the professionals (MDPCP): A Need of professional Communication for Professionals in India 1Dr.VivekMehrotra, 2Dr, Shiva - VivekMehrotra, Dr.; Durga, Shiva (International Journal of Psychosocial Rehabilitation, 2020)
--This paper is a delineate effort to introduce and develop a practiced based approach to professional communication termed as Multi-Dimensional Professional communication Programme for the Professionals (MDPCP).Communication is a process of transmitting feelings, attitudes, facts, believes and ideas between living beings. ELT education trend has recently become an eminent feature in the contemporary education phenomena as the concept of English Language Teaching (ELT) has immenselydeveloped over the last two decades. Particularly in Indiathe immense growth of multi- national market has enhanced the scope for professional communication, imbibing a vast area ranging from basic concepts of language to the contemporary professional or technical writing that encompasses written, oral, visual and digital communication within a workplace references.But having a glance of the contemporary market phenomena and considering the recruitment processes in the tremendously changing global market it has becomes rather essential to develop the conception of a practice-based approach (PBA) for English language teaching (ELT)for better outcomes that has been proposed here as Multi-Dimensional Professional communication Programme for the Professionals (MDPCP)